Unrelenting games: Multiple negotiations and landscape transformations in the tropical peatlands of Central Kalimantan, Indonesia - Sanders, A.J.P.; Ford, R.M.; Mulyani, L.; Prasti H., R.D.; Larson, A.M.; Jagau, Y.; Keenan, R.J. (Elsevier, 2019)
Land use change is often a result of negotiation between different interests. Focusing on negotiation practices helps to provide a nuanced understanding of land use change processes over time. We examine negotiations within a concession model for land development in the southern tropical peatlands of Central Kalimantan province in Indonesia. This region can be described as a ‘resource frontier’, where historical landscape transformations from large development projects and oil palm plantations intersect with state models of forest conservation and recent Reducing Emissions from Degradation and Forest Degradation (REDD+) projects. The study drew on actor-network theory (ANT) and combined an ethnographic approach with document analysis for understanding how these landscape transformations and land allocation for large concessions has left a legacy of continuing uncertainty and conflict over land. There is considerable gaming between actors to achieve their desired outcome. Increased competition for land and contested legal arrangements mean that the negotiations are virtually never-ending. ‘Winning’ at one stage of a negotiation may mean that those who feel they have lost will organise and use the system to challenge the outcomes. These findings show that attempts to implement pre-determined plans or apply global environmental goals at resource frontiers will become entangled in fluid and messy negotiations over land, rather than achieving any desired new status quo.